Recollection and amplified description of Euphorbia neorubella (Euphorbiaceae), a Critically Endangered succulent - Xin, Zhihao; Olukoye, Abiton; Belal, Hager R.; Mbuni, Yuvenalis Morara; Muchuku, John Kamau; Nyakudya, Elijah; Wang, Shengwei; Wei, Neng; Wang, Qingfeng (Phytotaxa, 2025)
Euphorbia neorubella is the most highly sought after species in the cultivation of succulent plants. Despite it being often grown by succulent plant collectors and in general horticulture, the species has not been collected from the wild since 1960. This paper reports on the recollection of E. neorubella from its type locality at Mbuinzau Hill in Kenya. The species is illustrated and an amplified description is presented. An identification key with which to separate E. neorubella from its close relatives is presented, and aspects of its distribution, habitat, and phenology are updated. Based on the IUCN Red List Categories and Criteria, the species is considered to be Critically Endangered (CR).